Experience of nurses in assessing postoperative pain in hip fracture patients suffering from dementia in nursing homes - Ferid Krupić; Mirza Bišćević; Emina Spahić; Amila Jašarević; Mahir Jašarević; Kemal Grbić; Eric Hamrin-Senorski; Eleonor Svantesson; Svemir Čustović; Olof Westin (Medicinski glasnik, 2019)
Aim: To explore the experiences of registered nurses in assessing postoperative pain in hip fracture patients suffering from dementia in nursing homes. Methods: The study was designed as a qualitative study using data from a self-reported questionnaire form. Data were collected through the self-administered questionnaire with 23 questions, mainly addressing demographic and social data, information about communication and pain assessment. Results: All nurses reported that large part of verbal communication with dementia patients was lost, and non-verbal communication was very important to optimize the care of these patients in postoperative situations. An assessment of pain in patients with dementia and hip fractures was a complex process because cognitive ability of these patients was reduced. Conclusion: Registered nurses need to know various and different forms of evaluation and tools to assess the experience of pain in patients with dementia who had undergone surgery for hip fractures. This is a complicated task, which requires a great deal of time, and means that nurses must work together with other medical staff, using a holistic approach.
Keywords: pain management; pain measurement; registered nurses; retirement